Musculoskeletal symptoms related to work environment - a report based on survey conducted among computer professionals - Żyga, Justyna (Journal of Education, Health and Sport, 2022)
Introduction Nowadays the computer has become an essential tool used at work in many vocations. Health effects resulting from sitting working are associated with taking the same position for a few hours every day. Although musculoskeletal disorders are widespread worldwide, they are typical for office jobs. Work related musculoskeletal disorders among the IT professionals are a common area of concern. Aim This study aimed to determine the prevalence of various musculoskeletal symptoms among computer workers. Results and Conclusions The survey was completed by 78 participants - 57 men (73,1%) and 21 women. Most participants (42,3%) were aged below 30 years. The musculoskeletal symptoms varied according to affected body area. Within the 7 days preceding the study, a substantial proportion of the participants reported lower back (44,9%), neck (43,6%), or shoulder (33,3%) symptoms. Almost one-quarter (23,1%) of the participants had upper back pain during the same period. Similarly, the same regions were the four most frequently affected in the 12 months preceding the study. Musculoskeletal symptoms were highly prevalent in the current sample. Prevention of the appearance and deterioration of symptoms is possible by following the rules of ergonomics at work with feedback regarding correct posture, frequently changing the position of the body with stretching exercises and taking active breaks.